2011
DOI: 10.1093/cercor/bhr099
|View full text |Cite
|
Sign up to set email alerts
|

Decoding Subject-Driven Cognitive States with Whole-Brain Connectivity Patterns

Abstract: Decoding specific cognitive states from brain activity constitutes a major goal of neuroscience. Previous studies of brain-state classification have focused largely on decoding brief, discrete events and have required the timing of these events to be known. To date, methods for decoding more continuous and purely subject-driven cognitive states have not been available. Here, we demonstrate that free-streaming subject-driven cognitive states can be decoded using a novel whole-brain functional connectivity analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

69
1,737
3
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,696 publications
(1,866 citation statements)
references
References 54 publications
69
1,737
3
7
Order By: Relevance
“…These networks of regions with coherent activity during rest are consistent across subjects and closely resemble the brain's functional organization of evoked responses (Damoiseaux et al, 2006;Fox and Raichle, 2007;Laird et al, 2011;Smith et al, 2009). Coherent BOLD activity persists during sleep and in anesthetized monkeys, suggesting that it reflects a fundamental property of the brain's functional organization (Larson-Prior et al, 2009;Vincent et al, 2007).Coherent BOLD activity, known as "functional connectivity" (FC), is modulated by learning (Bassett et al, 2011), cognitive and affective states (Cribben et al, 2012;Ekman et al, 2012;Eryilmaz et al, 2011;Richiardi et al, 2011;Shirer et al, 2012) and also spontaneously Chang and Glover, 2010; Kitzbichler et al, 2009). Chang andGlover (2010) showed that FC between the posterior cingulate cortex, a key region of the default mode network, and various other brain regions was highly dynamic over time.…”
mentioning
confidence: 59%
“…These networks of regions with coherent activity during rest are consistent across subjects and closely resemble the brain's functional organization of evoked responses (Damoiseaux et al, 2006;Fox and Raichle, 2007;Laird et al, 2011;Smith et al, 2009). Coherent BOLD activity persists during sleep and in anesthetized monkeys, suggesting that it reflects a fundamental property of the brain's functional organization (Larson-Prior et al, 2009;Vincent et al, 2007).Coherent BOLD activity, known as "functional connectivity" (FC), is modulated by learning (Bassett et al, 2011), cognitive and affective states (Cribben et al, 2012;Ekman et al, 2012;Eryilmaz et al, 2011;Richiardi et al, 2011;Shirer et al, 2012) and also spontaneously Chang and Glover, 2010; Kitzbichler et al, 2009). Chang andGlover (2010) showed that FC between the posterior cingulate cortex, a key region of the default mode network, and various other brain regions was highly dynamic over time.…”
mentioning
confidence: 59%
“…We selected these ROIs to evaluate functional connectivity in widespread brain areas considering distributed relevant functional networks. The Visual network in this study is the union of the ROIs from the High and Prime visual networks described by Shirer et al [2012]. …”
Section: Methodsmentioning
confidence: 99%
“…Functional relevance of each RSN was determined by assessing spatial overlap with the 90 functional regions of interest (ROI) defined by Shirer, Ryali, Rykhlevskaia, Menon, & Greicius (2012). RSN groups include subcortical (SBC), auditory (AUD), sensorimotor (SEN), cerebellum (CER), visual (VIS), salience (SAL), executive control (ECN), DMN, and language (LAN) brain regions.…”
Section: Methodsmentioning
confidence: 99%